The epitranscriptome in modulating spatiotemporal RNA translation in neuronal post-synaptic function - Hussain, Shobbir; Bashir, Zafar I. (Frontiers in Cellular Neuroscience, 2015)
The application of next-generation-sequencing based methods has recently allowed the sequence-specific occurrence of RNA modifications to be investigated in transcriptome-wide settings. This has led to the emergence of a new field of molecular genetics research termed ‘epitranscriptomics’. Investigations have shown that these modifications can exert control over protein synthesis via various mechanisms, and particularly when occurring on messenger RNAs, can be dynamically regulated. Here, we propose that RNA modifications may be a critical regulator over the spatiotemporal control of protein-synthesis in neurons, which is supported by our finding that the RNA methylase NSun2 colocalises with the translational-repressor FMRP at neuronal dendrites. We also observe that NSun2 commonly methylates mRNAs which encode components of the postsynaptic proteome, and further find that NSun2 and FMRP likely share a common subset of mRNA targets which include those that are known to be translated at dendrites in an activity-dependent manner. We consider potential roles for RNA modifications in space- time- and activity-dependent regulation of protein synthesis in neuronal physiology, with a particular focus on synaptic plasticity modulation.